2011
DOI: 10.1177/0021998310378906
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the composites produced from co-weaved poly ether ether ketone and glass fiber fabric

Abstract: The extruded poly ether ether ketone (PEEK) and glass fiber yarns were used to obtain the co-weaved hybrid fiber fabrics. Compression molding technique was employed to obtain the glass-PEEK composites from the hybrid fiber fabric. Composites having different thickness values of 3.3, 3.6, and 4.5 mm have been fabricated by varying the number of layers (15, 17, and 20 layers) of co-weaved fabrics. The mechanical properties such as flexural strength and inter laminar shear strength as a function of number of laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…This method enables to wet the fiber with the matrix. However, this method also has some defects, Fujihara et al 15 indicated that the matrix powders can be easily dislodged from the reinforcing filaments, unless a heat-resistant adhesive—that is used for letting the matrix powders stick to the surface of fiber—is used but that will affect the performance of composites. (4) Co-woven method 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…This method enables to wet the fiber with the matrix. However, this method also has some defects, Fujihara et al 15 indicated that the matrix powders can be easily dislodged from the reinforcing filaments, unless a heat-resistant adhesive—that is used for letting the matrix powders stick to the surface of fiber—is used but that will affect the performance of composites. (4) Co-woven method 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…It was stated that the high impact properties achieved may be attributed to the modulus of yarn systems and better fiber–matrix adhesion. 25…”
Section: Introductionmentioning
confidence: 99%
“…Some detailed studies were performed by researchers about the mechanical and impact properties of hybrid composites. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Swolfs et al 8 reviewed the basic mechanisms of hybrid effects to obtain the optimal design of hybrid composites. Strait et al 9 stated that there were no effects of stacking sequence, and reinforcement form was observed in terms of energy after peak load in carbon fiber-reinforced thermoplastic toughened by the hybrid epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many workers 9 18 carried out investigations on continuous glass fiber–reinforced polypropylene composites (CGF/PP) from commingled yarn. However, there are very few reports 1920 on CGF/PEEK composites from commingled yarn, since the high melt viscosity of PEEK and high molding temperature, make it difficult to process. However, these difficulties cannot undermine the advantages of PEEK.…”
Section: Introductionmentioning
confidence: 99%